Overcoming scarring in the urethra: Challenges for tissue engineering - Abdulmuttalip Simsek; Reem Aldamanhori; Christopher R. Chapple; Sheila MacNeil (Asian Journal of Urology)
Urethral stricture disease is increasingly common occurring in about 1% of males over the age of 55. The stricture tissue is rich in myofibroblasts and multi-nucleated giant cells which are thought to be related to stricture formation and collagen synthesis. An increase in collagen is associated with the loss of the normal vasculature of the normal urethra. The actual incidence differs based on worldwide populations, geography, and income. The stricture aetiology, location, length and patient's age and comorbidity are important in deciding the course of treatment. In this review we aim to summarise the existing knowledge of the aetiology of urethral strictures, review current treatment regimens, and present the challenges of using tissue-engineered buccal mucosa (TEBM) to repair scarring of the urethra. In asking this question we are also mindful that recurrent fibrosis occurs in other tissues—how can we learn from these other pathologies? Keywords: Urethral strictures, Fibrosis, Tissue-engineered buccal mucosa, Augmentation urethroplasty